Numerical Simulation of Microwave-Induced Cracking of Coal Containing Pyrite Powder Based on a Multi-Field Coupling Model - Yidu Hong; Shengyi Long; Xiaowan Sun (Applied Sciences)
Microwave irradiation has become a potential technical method for coalbed degassing, which can effectively improve its permeability. A coupled electromagnetic—thermomechanical damage (ETMD) model was established to study the damage characteristics of coal containing pyrites. Under microwave irradiation, the temperature increase rate of pyrite was significantly higher compared to the coal matrix. The coal matrix was cracked by expansion stress in high-temperature spots. In the rotational heating mode, the coal matrix was easier to damage than under the static heating mode. The coal matrix damage efficiency was also related to the position of the sample under the static heating mode. Uniform centripetal pressure could inhibit coal matrix damage. Moreover, the pressure distribution affected the damage paths. Compared to no confining pressure, the percentage of areas damaged in coal was lower under low parallel pressure and higher under high parallel pressure.